2019
DOI: 10.1093/annonc/mdy505
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral IL17-producing cells infiltration correlate with antitumor immune contexture and improved response to adjuvant chemotherapy in gastric cancer

Abstract: Background: Tumor IL17-producing (IL17A þ) cells infiltration has different prognostic values among various cancers. The objective of this study was to assess the effect of IL17A þ cells in gastric cancer. Patients and methods: The study included two patient cohorts, the Cancer Genome Atlas cohort (TCGA, n ¼ 351) and the Zhongshan Hospital cohort (ZSHC, n ¼ 458). The TCGA and ZSHC were used for mRNA-related and cells infiltration-related analyses, respectively. The roles of IL17A mRNA and IL17A þ cells in over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 33 publications
7
53
0
Order By: Relevance
“…However, in the present study, there were no significant correlations between IL‐17‐producing cells and DFS. Although the discrepancy might be as a result of the limited sample of NSCLC patients, it has been reported that higher intratumoral IL‐17A + cells were associated with better OS in patients with gastric cancer who received adjuvant chemotherapy, and γδT17 cells could enhance the efficacy of anticancer chemotherapy, indicating that IL‐17‐producing cells in NSCLC patients may contribute to cancer therapy, resulting in the prolonged OS. In our case, we found that patients who underwent surgery had better OS compared to patients who received chemotherapy (Figure A‐C).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, there were no significant correlations between IL‐17‐producing cells and DFS. Although the discrepancy might be as a result of the limited sample of NSCLC patients, it has been reported that higher intratumoral IL‐17A + cells were associated with better OS in patients with gastric cancer who received adjuvant chemotherapy, and γδT17 cells could enhance the efficacy of anticancer chemotherapy, indicating that IL‐17‐producing cells in NSCLC patients may contribute to cancer therapy, resulting in the prolonged OS. In our case, we found that patients who underwent surgery had better OS compared to patients who received chemotherapy (Figure A‐C).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor‐infiltrating lymphocytes have been shown to be a determinant of carcinogenesis and progression, and may also serve as a predictor of patient response to neoadjuvant chemotherapy . Wang et al reported that IL‐17A + immune cell infiltration was correlated with antitumor immune contexture and improved response to adjuvant chemotherapy in gastric cancer. In addition, Nywening et al revealed that dual targeting of tumor‐associated CCR2 + macrophages and CXCR2 + neutrophils could improve chemotherapeutic responses and enhance antitumor immunity by disrupting myeloid recruitment in pancreatic ductal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…34 Infiltrating lymphocytes (IL)17Aþ cells infiltration could be used as an independent prognostic biomarker for OS and predictive biomarker for superior response to adjuvant chemotherapy. 35 Stromal immunotype predict survival and benefit from adjuvant chemotherapy in patients with muscle-invasive bladder cancer. 36 TIL, immunotype might predict the response to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%